Essentials of Christian theology - Grenz, Stanley J. (Stanley James), 1950-2005.; Placher, William C. (William Carl), 1948-2008. (Louisville, Kentucky, Westminster John Knox Press(WJK), 2003)
"Presenting two dialoguing essays on each of nine foremost theological questions, William Placher has provided an introductory reader in theology, giving a discussion of the history and current state of each doctrinal issue, he allows the essays to explore and raise questions about their key elements - and the contemporary issues confronting them."--Jacket
Why bother with theology? : an introduction / William C. Placher -- How do we know what to believe? : revelation and authority / Stanley J. Grenz, Noel Leo Erskine --
Includes bibliographical references and index
Keywords: Theology, Doctrinal -- Popular works; Faculty publications -- 2003; Essays; Popular works